SWOT Analysis on Bang Anwar Young Coconut Ice MSMEs - Laila Najwa; Tyna Yunita; Nabila Dwi Putri; Nasywa Alifia Gusnarni; Rosa Auliya Ananda (Siber International Journal of Sport Education, 2025)
The results of the study show a development strategy that can increase the competitiveness of Bang Anwar's Es Kelapa Muda MSMEs, which have been operating since 2006, with an average daily income of around IDR 300,000 and a monthly income of around IDR 1,000,000. This research focuses on internal and external factors of the company, and uses a qualitative descriptive approach to literature research. Fresh flavors, affordable prices, and simple production processes are strengths, according to the analysis. The limitations of raw materials and product variety are two drawbacks. High local demand provides opportunities, while modern competition and weak coconut prices pose a threat. Partnerships, increased production, product diversification, and digital marketing are some of the suggested strategies. As a result, SWOT analysis can be a strategic tool for small and medium-sized companies looking to change and grow sustainably.